Fruit set in perennial vetch (Vicia unijuga): reproductive system and insect role in pollination. (23rd March 2015) - Shen, Z.‐W.; Matthew, C.; Nan, Z.‐B.; Wang, Y.‐R.
Abstract: Perennial vetch ( Vicia unijuga ) is a wild plant found in parts of East Asia and potentially valuable as a forage species for more extreme environments. Information on its reproductive system and pollination biology is needed for progress in domestication of the species. We characterized the reproductive system of perennial vetch as facultative xenogamy (i.e. it is largely cross‐pollinated by insects but is also self‐compatible and can self‐pollinate). There was no significant difference (P > 0.05) in the fruit set ratio between insect cross‐pollination and artificial cross‐pollination at the seed maturation stage, but natural self‐pollination was inefficient. In our study conducted on the Tibetan plateau, eight insect species (especially certain bumble bees) are identified as potential pollinators, and four other insect species belonging to the Lepidoptera and Diptera visited flowers but are unlikely to be pollinators. The flower visitation rate of wild bumble bees was 1.6–3.3 times higher than domestic honeybees, with Bombus lepidus having the highest visitation rate of 15.7 florets/min. The diurnal floret opening rhythm of perennial vetch was synchronized with diurnal activity of potential pollinators. Optimal pollination of perennial vetch would likely be achieved using wild bees, as they have behaviour characteristics and flower tripping ability necessary, and are present in sufficient numbers to be efficient pollinators of this crop. However, even with sufficiency of pollination, there remains a fundamental problem with low fruit set which requires further investigation from a plant biology perspective.